2021
DOI: 10.1111/ijac.13822
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nonlinear regression model of cutting force for C/SiC composites by laser‐assisted micromachining

Abstract: Based on the response surface methodology (RSM), laser‐assisted micromachining (LAMM) experiments of carbon fiber reinforced silicon carbide matrix(C/SiC) composites have been carried out to obtain the data of three‐direction cutting forces Fx, Fy, Fz, and result‐force F in the cutting process. A stepwise regression method is used to screen out the factors that significantly affected the cutting force, and hence a multivariate nonlinear mathematical regression model has been established. Through the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…RSM is considered an efficacious statistical tool that is mainly employed for experimental design, mathematical modeling, and optimization [ 43 ]. RSM assists in the evaluation of responses that are affected by one or more factors [ 44 ]. Face-centered central composite design (FCCD), a subset of RSM, was used to statistically examine the effects of the independent parameters, namely, the BOF ratio and the molarity of NaOH, on the dependent variables: flow values, compressive strength, flexural strength, and water absorption.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…RSM is considered an efficacious statistical tool that is mainly employed for experimental design, mathematical modeling, and optimization [ 43 ]. RSM assists in the evaluation of responses that are affected by one or more factors [ 44 ]. Face-centered central composite design (FCCD), a subset of RSM, was used to statistically examine the effects of the independent parameters, namely, the BOF ratio and the molarity of NaOH, on the dependent variables: flow values, compressive strength, flexural strength, and water absorption.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…LAM can efficiently cut a variety of hard and brittle materials [17], such as engineering ceramics [18], hardened steels [19], metal matrix composites [20] and so on. LAM uses the thermal effect of a laser beam to soften the cutting area of the material to be processed, and the yield strength, cutting force and tool wear can be reduced [21]. LAM has gradually become the most recognized thermal auxiliary machining technology, which can improve machining quality and efficiency for hard and brittle materials [22].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al investigated the effect of spindle speed, feed speed, cutting depth, and laser pulse duty ratio on the cutting force of laser-assisted turning fused quartz based on the Taguchi method and RSM, and the experimental results showed that the optimal parameter combination of RSM generates a smaller cutting force and better surface integrity in the process of laser-assisted turning of fused silica [ 18 ]. Zhai et al conducted laser-assisted micromachining experiments on carbon fiber reinforced silicon carbide matrix (C/SiC) composites based on the response surface method, and investigated the effect of laser power, cutting speed, and cutting depth on cutting force, and obtained the mathematical prediction model of cutting force F x , F y , F z in three directions in the cutting process [ 19 ]. Conventional turning and laser-assisted turning experiments on SiC-Al2O3 reinforced aluminum hybrid nanocomposites were carried out by Reza et al, and the laser power, cutting depth, and cutting speed were optimized based on the Taguchi method to find the smallest surface roughness and cutting force.…”
Section: Introductionmentioning
confidence: 99%